2022
DOI: 10.3847/2041-8213/ac9977
|View full text |Cite
|
Sign up to set email alerts
|

Water and an Escaping Helium Tail Detected in the Hazy and Methane-depleted Atmosphere of HAT-P-18b from JWST NIRISS/SOSS

Abstract: JWST is here. The early release observation (ERO) program provides us with the first look at the scientific data and the spectral capabilities. One of the targets from the ERO is HAT-P-18b, an inflated Saturn-mass planet with an equilibrium temperature of ∼850 K. We present the NIRISS/SOSS transmission spectrum of HAT-P-18b from 0.6 to 2.8 μm and reveal the planet in the infrared beyond 1.6 μm for the first time. From the spectrum, we see clear water and escaping helium tail features in an otherwise very hazy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 49 publications
2
21
0
Order By: Relevance
“…With the successful launch and operations of JWST, we now have access to an extremely precise near-IR space telescope that can potentially give us access to observations of escaping He in sub-Jovian worlds. Fu et al (2022) demonstrated that the NIRISS spectrograph can detect metastable He in the atmosphere of the hot Saturn HAT-P-18 b. This not only confirms the previous detection from ground-based narrowband photometry (Paragas et al 2021), but also reveals the presence of a potential He tail trailing the planet (similar to the case of WASP-107 b; Spake et al 2021).…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…With the successful launch and operations of JWST, we now have access to an extremely precise near-IR space telescope that can potentially give us access to observations of escaping He in sub-Jovian worlds. Fu et al (2022) demonstrated that the NIRISS spectrograph can detect metastable He in the atmosphere of the hot Saturn HAT-P-18 b. This not only confirms the previous detection from ground-based narrowband photometry (Paragas et al 2021), but also reveals the presence of a potential He tail trailing the planet (similar to the case of WASP-107 b; Spake et al 2021).…”
Section: Introductionsupporting
confidence: 82%
“…In order to estimate the observable signal, we first need to convolve this theoretical spectrum to the line-spread function (LSF) of the instrument, bin the spectrum to its native wavelength grid, and estimate its uncertainties. For the NIRISS/SOSS LSF, we used the same value used to analyze the He signal in HAT-P-18 b presented in Fu et al (2022), and which gave good qualitative agreement with the observed signal. For the NIRSpec G140M and G140H modes, we estimated the LSF using an observation from commissioning program PID 1128 (PI: Luetzgendorf) 8 .…”
mentioning
confidence: 99%
“… 2018 ; Fu et al. 2022 ). We observed the hot Neptune HAT-P-11b with HST /WFC3 between μm and found the signature of helium absorption in its upper atmosphere (Mansfield et al.…”
Section: Atmospheric Escape From the Highly Irradiated Exoplanet Hat-...mentioning
confidence: 99%
“…Bottom: the resulting transmission spectrum (orange line) of this planet is shaped considerably by haze with some strong methane features permeating through the haze at longer wavelengths. The teal line shows the transmission spectrum of the same planet but with the haze opacity artificially removed, while the transparent colored line shows these data at a spectral resolution of R = 1000. enough to host considerable CH 4 in their atmospheres via thermochemical equilibrium considerations have not produced detectable features (Stevenson et al 2010;Benneke et al 2019;Fu et al 2022). What few observational searches for CH 4 that do appear in the literature (e.g., Swain et al 2008;Guilluy et al 2019;Giacobbe et al 2021;Bézard et al 2022) have been called into question by other works or have not been reproduced.…”
Section: Current Exoplanet Landscapementioning
confidence: 99%